Microlanguages: One Way to Contribute to an Educational Relationship with Children and Youth in a Pedagogies of the South Framework - Contreras-Salinas, S (UNIV COSTA RICA, EDITORIAL, 2020)
Contributing to the reality of children and youngsters within the pedagogies of the South is a complex and contradictory endeavor. It is for this reason, that this essay seeks to contribute to the daily efforts involved in pedagogical practices. Thus, pedagogies that are critical of the south, emerge as an expression that accounts for a field of knowledge considered to be an alternative to hegemonic educational approaches and establishing itself as a teaching alternative in lieu of questioning experience and perceived as a practical social policy. The resulting prerogative is that adults are the dominant group over children and youngsters, many times pushing them to a culture of silence, particularly in school settings and undoubtedly, a pending item, yet to be addressed in Latin America. This article addresses the figures of speech that arise in our daily life experience, particularly tropes or sayings, which help us mold our objectivity and subjectivity. This is exemplified by tropes used in Spanish slang used by youngsters in Chile, namely, "Are you still alive?" (ser vivo) and "Are you a gallery?" (ser galeria). It can be concluded that although tropes have not undone colonial linkages, they help access values by exploring power relationships. For that reason, pedagogical language should contemplate these power struggles and instill in children and youngsters, linguistic skills to prevent them from turning into zombies and live their lives solely on their outlook towards the future.